Hubungan Tingkat Pengetahuan Pemakaian Lensa Kontak dengan Kejadian Iritasi Mata pada Mahasiswa Fakultas Hukum Universitas Tarumanagara - Alifah Nisrina; Meriana Rasyid (Jurnal Kesehatan, 2022)
Humans can perform daily activities if they have healthy eyes. A contact lens is a visual aid that is located on the surface of the cornea. The weakness of using contact lenses that often occurs depends on many factors, namely compliance, understanding, and procedures for using contact lenses. The purpose of this study was to determine the relationship between the level of knowledge of the use of contact lenses with the incidence of eye irritation in students of the Faculty of Law, Tarumanagara University. The method used in this study is an observational analytic study with a cross-sectional design. The research was conducted at the Faculty of Law, Tarumanagara University in June-September 2021. The research sample was 171 students. Data were analyzed using SPSS with chi-square analysis. The results of this study indicate that most of the student's knowledge level of contact lens use is moderate as many as 101 people (49.5%). Most students experienced eye irritation as many as 168 people (82.4%). The results show a p-value of 0.000, where the p-value <0.05 means that there is a relationship between the level of knowledge of the use of contact lenses and the incidence of eye irritation in students of the Faculty of Law, Tarumanagara University.